Perubahan Hemodinamika Pada Pasien Yang Dilakukan Terapi Hemodialisa Di Ruang Hemodialisa RSUD Dr. Moewardi - Endah Dwi Maharsi; Hartono Hartono (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Hemodynamic, Hemodyalisis. According to calculation of Pernefri on 2013, there are about 19.621 chronic renal failure patients which they need routine hemodialysis, over of 53% of patients is under 54 years old. Recently, hemodialysis treatment get rapidly developing, but there are many health problem on patients when they get hemodialysis treatment. Patients often get some complication such as hemodynamic problem. The purpose of this research is to 1) to discribe the characteristics of the gender, age 2) to discribe the hemodynamic (sistole, diastole, MAP, RR, HR) of pre and post hemodialysis 3) to analize the hemodynamic changes pre and post hempdyalisis treatment. This type of research is quasy experiment with one group pretest – posttest design. The results of the research is there are hemodynamic changes in patients done hemodyalisis at the hemodialysis unit in Dr. Moewardi Hospital of Surakarta. This is proven by testing paired samples t-test (systole, MAP, HR) which obtained the value of p < 0,05 and wilcoxon test (diastole, RR) which obtained the value of p < 0,05. According to the test of paired samples t-test and Wilcoxon test if p < 0,05, then the provision of therapy hemodialysis influential to changes in blood pressure. Conclusion. There is hemodynamic changes in patient done hemodyalisis at the hemodialysis unit dr.Moewardi Hospital.